Implementasi WPA2 Enterprise dan LDAP Dalam Membangun Sistem Informasi Kehadiran Karyawan - Prismana, IGL Putra Eka; Permadi, Ginanjar Setyo; Khamdani, Wahyu (JSINBIS (Jurnal Sistem Informasi Bisnis), 2020)
Technological developments have a positive effect on agencies and companies, one of which is the innovation of employee attendance registration using the internet network media. Employee attendance system model using internet network will certainly make it easier to control employee attendance. The internet network is an important part of every agency in helping its performance and can also be used as an attendance system. WPA2 Enterprise implementation is used as authentication using the provided email and password. Devices that have been connected to the network will automatically be recorded in the employee attendance system. The implementation of WPA2 Enterprise requires freeradius assistance in processing authentication data from employees which will then be verified again through LDAP, in this case UNESA uses Google LDAP. The attendance system by implementing WPA2 Enterprise has been tested by implementing the Technology Acceptance Model (TAM) method resulting in 43% answering strongly agree and 56% answering agreeing. The analysis is based on 78 employees who gave their assessments. Based on the results of the acceptance analysis of the system, it is stated that it can be applied at UNESA.